Unveiling Pachacamac : new hypotheses for an old Andean sanctuary - Marcone, Gian Carlo (University Press of Florida, 2022)
"This volume synthesizes 25 years of new data and hypotheses on the sacred Andean site of Pachacamac, a sanctuary that has an enduring presence in Peruvian history and plays a pivotal role in the formation of current views about religion and thought in the pre-Hispanic period"--